When Geopolitics and Architecture Touch : The Micropolitics Surrounding Architectural Negotiations in the Great Mosque of Rome - Daniele Campobenedetto; Giulia Massenz (Fabrizio Serra, 2024)
This paper examines the Great Mosque of Rome, as well as the broader trend of Islamic architectural experimentation in Western cities, within the context of international relations between Europe and the Arab world up until the mid-1970s. It provides an overview of the building’s design, with an emphasis on the interactions among institutions, clients, and designers that took place in this process. The paper presents the two groups of designers shortlisted for the mosque’s design – Portoghesi and Gigliotti on one side, and Sami Mousawi on the other – as representing two distinct cultural worlds. It then traces the development from the initial competition design by Portoghesi and Gigliotti to the final realisation in collaboration with the Anglo-Iraqi architect Mousawi. Key changes in Islamic architectural elements, such as the introduction of the dome and minaret, are then analysed, with the findings supporting Stefano Allievi and Carmelo Russo’s arguments about the mosque’s political significance. The approach of this study is to apply architectural analysis as a tool to investigate and substantiate broader insights into the sociological, cultural, and political fields surrounding such developments.